Factors affecting participation of seed growers in Ginintuang Masaganang Ani (GMA) rice program the case of Leyte Province - Sala, Fe V. (University of the Philippines in the Visayas, 2005)
The study was conducted in order to assess the participation of accredited rice seed growers in the province of Leyte relative to the implementation of the certified rice seed subsidy component of the GMA Rice Program, implemented in May 2000 up to April 2004. Specifically, the study aimed to: 1) describe the socio demographic characteristics of the accredited seed growers in Leyte; 2) identify the seed production practices adapted by seed growers; 3)determine the extent of seed grower's participation in the certified rice seed subsidy component of GMA-Rice Program; 4) find out the problems encountered by seed growers in the implementation of the program; 5) determine the factors that affect seed growers participation in the GMA Rica Program; and 6) recommend to the Office of the Provincial Agriculturist and the Department of Agriculture planners sound policies i order to come up with a sustainable rice seed supply in the province. A pre-tested interview schedule was used to gather the necessary data and these were analyzed using descriptive statistics such as frequency counts, percentages, averages, range and standard deviation.Majority of the respondents (80%) from the participating group planted their seed farms twice a year but non-participating group (20%) planted only for one cropping season during the GMA Rice Program implementation. The majority of the seed growers from the participating group practiced straight-row planting with a planting distance of 20 x20 cm using 2-3 seedlings per hill. Ninety five percent of the respondents applied basal fertilizers, using complete and organic fertilizers at the rate of two bags mixed with one bag of urea per hectare. For topdressing, they used two bags of urea per hectare. the most widely used rice varieties were PSBRC-18 and PSBRC-74. In order to assure the purity of the seeds produced, seed growers rouged their seed farms three times from the vegetative to the ripening stages. Both the participating and non-participating groups reported that they dried and cleaned their seeds at an average of 3 times per cropping. This operations make seed production very tedious, labor intensive and expensive, especially if one lacks the needed post-harvest facilities. No seed growers reported that they were the ones who collected the seed samples for laboratory analysis. They said that their assigned seed nspectors to their area collected the samples, including tagging of the seeds. They reported, however, that there were cases when seed inspectors requested them to assist especially when there is a large volume of seeds to be tagged but they were duly supervised by these inspectors. Most common problemss mentioned by the participating group included DA's delayed payment for their seeds and delayed results of their seed laboratory analysis from the Seed Quality Control Services. There were also 90% who siad that the payment, which was in the form of a check, is disadvantageous to them because this check has still to be deposited in the bank for at least two weeks before they are able to use the money. On the other hand, respondents from the non-participating group considered the pre-planting and production aspects, like insufficiency of irrigation water (100%) and lack of post-harvest facilities (60%) as among the major problems respectively affecting their participation in the program. Some (53%) also reported that lack of capital or absence of financial assistance as the major reason for their non-participation in the program. Based on the above findngs, it is recommended that factor such as sustained irrigation, ownership of post-harvest facilities, values re-orientation training and financial capability of the seed growers must be included as important considerations in accrediting new seed growers. The Department of Agriculture should facilitate seed production by providing accessible planting materials to seed growers and through an efficient and fast release of the results of seed laboratory analysis. Payment system in procuring of seeds must be made without delay in order to encourage more seed growers to participate. Most importantly, regular or periodic consultative meetings with the program implementers, beneficiaries and other concerned agencies must be conducted. This is one way to monitor the extent of the program's implementation threshing out problems met, and provide immediate solutions to impeding problems. This will also serve as an avenue to get feedbacks and comments from the different implementing sectors which guide management in its policy decisions.